2019
DOI: 10.1101/833871
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serum proteomics expands on high-affinity antibodies in immunized rabbits than deep B-cell repertoire sequencing alone

Abstract: Rabbits are a model for immunology studies, and monoclonal antibodies developed from rabbits have been highly sought after to empower immunoassays in a variety of other applications. Highthroughput characterization of circulating serum antibodies in response to specific antigens is highly impactful for both immunology studies and antibody development. A combination of high throughput sequencing of antibody transcripts from B cells and proteomic analysis of serum antibodies, referred to as immunoproteogenomics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Safonova and colleagues could show that adapting the analysis from quantification of identical antibody sequences to that of antibody clones (antibody sequences belonging to the same lineage) at least partially restored the correlation between genomics-and proteomics-based quantification [46]. Nevertheless, Bonissone and colleagues provided evidence supporting the claims by Cheung and colleagues showing that serum antigen-specific clones are not among the most abundant BCR clones as sequenced from blood, bone marrow, or spleen [42]. Follow-up studies are necessary to elucidate to what extent each lymphoid organ contributes to the blood, mucosal, and central nervous system (CNS) antibody repertoire [39,47].…”
Section: Extent Of Overlap Of Genomic Bcr and Proteomic Antibody Repertoiresmentioning
confidence: 96%
See 2 more Smart Citations
“…Safonova and colleagues could show that adapting the analysis from quantification of identical antibody sequences to that of antibody clones (antibody sequences belonging to the same lineage) at least partially restored the correlation between genomics-and proteomics-based quantification [46]. Nevertheless, Bonissone and colleagues provided evidence supporting the claims by Cheung and colleagues showing that serum antigen-specific clones are not among the most abundant BCR clones as sequenced from blood, bone marrow, or spleen [42]. Follow-up studies are necessary to elucidate to what extent each lymphoid organ contributes to the blood, mucosal, and central nervous system (CNS) antibody repertoire [39,47].…”
Section: Extent Of Overlap Of Genomic Bcr and Proteomic Antibody Repertoiresmentioning
confidence: 96%
“…Acquiring these statistics of antibody repertoire concentration dynamics is crucial as antibodies provide long-lived protection [40] and their concentration has been linked to antibody neutralization efficacy [41]. Interestingly, Bonissone and colleagues showed that, in rabbits, ~27% of heavy and ~15% of light-chain clones were exclusively observed in bone marrow or spleen, and not in the blood-borne B cell population [42]. Nevertheless, they showed that the lack of access to major ASC locales such as the bone marrow and spleen, and thus the lack of sequence coverage of the main ASC subsets responsible for the secretion of the antigen-specific antibody repertoire, may at least partly be remedied by assembling a sequence DB that encompasses BCR-seq data at several timepoints throughout immunization [42].…”
Section: Trends In Biotechnologymentioning
confidence: 99%
See 1 more Smart Citation
“…We used the proprietary proteogenomic platform Alicanto for data analysis and visualization (25). 1,512 paired heavy and light chain antibody sequences derived from antigen-sorted memory B cells were analyzed directly by Alicanto.…”
Section: Proteo-genomic Data Analysismentioning
confidence: 99%
“…We recently described a proteo-genomic approach for identifying sequences of antigen-specific polyclonal antibodies in animal serum (25) and reported methods for large-scale antiviral human mAb discovery from the memory B cell repertoire (26). In this study, we characterize the circulating antibody response to ebolavirus GPs at the molecular level by identifying mAbs that are present in convalescent plasma collected from an EVD survivor (Figure 1).…”
mentioning
confidence: 99%